Respuesta :

Simplifying
7x + -11 = 17 + -7x

Reorder the terms:
-11 + 7x = 17 + -7x

Solving
-11 + 7x = 17 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-11 + 7x + 7x = 17 + -7x + 7x

Combine like terms: 7x + 7x = 14x
-11 + 14x = 17 + -7x + 7x

Combine like terms: -7x + 7x = 0
-11 + 14x = 17 + 0
-11 + 14x = 17

Add '11' to each side of the equation.
-11 + 11 + 14x = 17 + 11

Combine like terms: -11 + 11 = 0
0 + 14x = 17 + 11
14x = 17 + 11

Combine like terms: 17 + 11 = 28
14x = 28

Divide each side by '14'.
x = 2

Simplifying
x = 2
7x-11 = 17-7x
7x+7x = 17+11
14x = 28
x = 2

you needbi change the aritmathical sign when the number passed equal sign

sorry if I have a bad grammar